Bridging agro-science and human nutrition: zinc nanoparticles and biochar as catalysts for enhanced crop productivity and biofortification - Ahmed, Nazir; Deng, Lifang; Narejo, Mehar-un-Nisa; Baloch, Iqra; Deng, Lansheng; Chachar, Sadaruddin; Li, Yongquan; Li, Juan; Bozdar, Bilquees; Chachar, Zaid; Hayat, Faisal; Chachar, Muzafaruddin; et al. (Frontiers in Plant Science, 2024)
The integration of zinc nanoparticles (Zn NPs) with biochar offers a transformative approach to sustainable agriculture by enhancing plant productivity and human nutrition. This combination improves soil health, optimizes nutrient uptake, and increases resilience to environmental stressors, leading to superior crop performance. Our literature review shows that combining Zn NPs with biochar significantly boosts the crop nutrient composition, including proteins, vitamins, sugars, and secondary metabolites. This enhancement improves the plant tolerance to environmental challenges, crop quality, and shelf life. This technique addresses the global issue of Zn deficiency by biofortifying food crops with increased Zn levels, such as mung beans, lettuce, tomatoes, wheat, maize, rice, citrus, apples, and microgreens. Additionally, Zn NPs and biochar improve soil properties by enhancing water retention, cation exchange capacity (CEC), and microbial activity, making soils more fertile and productive. The porous structure of biochar facilitates the slow and sustained release of Zn, ensuring its bioavailability over extended periods and reducing the need for frequent fertilizer applications. This synergy promotes sustainable agricultural practices and reduces the environmental footprint of the traditional farming methods. However, potential ecological risks such as biomagnification, nanoparticle accumulation, and toxicity require careful consideration. Comprehensive risk assessments and management strategies are essential to ensure that agricultural benefits do not compromise the environmental or human health. Future research should focus on sustainable practices for deploying Zn NPs in agriculture, balancing food security and ecological integrity and positioning this approach as a viable solution for nutrient-efficient and sustainable agriculture.